Differential functionalisation of the internal and external surfaces of carbon-stabilised nanoporous silicon. Issue 55 (21st June 2019) - Alba, Maria; Robin, Morgane; Menzies, Donna; Gengenbach, Thomas R.; Prieto-Simon, Beatriz; Voelcker, Nicolas H.
Abstract : A versatile strategy to differentiate the surface chemistry of the internal and external pore walls of highly-stable nanoporous silicon. Abstract : We report the first method to introduce differential functionalities in the interior pore walls and exterior surface of highly stable thermally hydrocarbonised porous silicon (THCpSi) films. The approach exploits the hydrophobicity of the hydrosilylated THCpSi to, first, selectively functionalise the external surface, and subsequently derivatise the hydrophobic internal pore walls.